How I Do It: New Dissector Device Allows for Effective Operative Field in Transoral Endoscopic Thyroid Surgery Using Vestibular Approach. (October 2018) - Müller, Verena; Mogl, Martina; Seika, Philippa; Jöns, Thomas; Sauer, Igor; Pratschke, Johann; Anuwong, Angkoon; Zorron, Ricardo
Background . Minimally invasive thyroid and parathyroid resections are rarely performed. Promising new endoscopic transoral approaches to the anterior neck (transoral endoscopic thyroidectomy vestibular approach [TOETVA]) have been described with good results and few complications. This study evaluates a new device to allow the safe entrance of trocars in the subplatysmal space for TOETVA in a cadaver model. Methods . The technique was performed in 4 unilateral thyroidectomies in female cadavers. The technical steps consisted of a 10-mm incision made at the center of the oral vestibule followed by subplatysmal hydrodissection. The blunt dissector is a metallic stick with an olive at the end and promotes progressive gain in subplatysmal space enlarging the operative field. The instrument was inserted creating a space below the platysma to the anterior neck and the strap muscles. Three trocars were inserted in the vestibular area. The dissection begins by cutting the linea alba cervicalis. The isthmus was dissected and transected. Anatomical structures as the superior thyroid artery, parathyroid glands, and the recurrent laryngeal nerve could be safely identified with magnified vision. Results . Optimal operative field due to subplatysmal dissection by the device allowed for exposition of thyroid and parathyroid glands in all cases. Unilateral thyroidectomy was performed in a mean of 54 minutes with excellent aesthetic results. Conclusions . The new device is a promising feature to allow safe transoral thyroid surgery in a cadaver model. Further studies in clinical series are needed to evaluate the broad application of the device.